Ill or Evil: comparative analysis of the defence of unsoundness of mind in England, India, and Sri Lanka - Niriella, M.A.D.S.J.S. (Faculty of Law, University of Colombo, 2021)
Mental illness is not an uncommon phenomenon. As found by the medical research studies Psychotics are more prone to abnormal behavior including criminality. Unsoundness of mind is recognized as a general defence that can be claimed by an accused of any offence. In every judicial system in the world, a successful plea results not in a normal acquittal but in the qualified acquittal that the defendant is not guilty by reasons of unsoundness of mind. Section 77 of the Penal Code which is based on the age-old M'Naghten rules is the only legal provision in the criminal law of Sri Lanka that permits an accused to claim the defence of unsoundness of mind. There is a concern among the academics in the field of law and some legal practitioners as to whether the law specified in this provision is sufficient to cover all forms of psychological disorder situations. The objective of this study is to critically analyze the law relating to insanity defence in Sri Lanka whilst comparing our law with India and England. It also suggests reforms to the existing criminal law in Sri Lanka to cover all forms of psychological disorder and abnormal conditions of a person which resulted in criminal behavior. This research is mainly a doctrinal study consists of a conceptual analysis of section 77 of the Penal Code and Supreme Court judgments pronounced from 1948 to date on the cases of the insanity defence. To achieve the main objective, this study further reviews the law relating to the defence of unsoundness of mind available in India and England. Information gathered from Psychiatrists, judges, lawyers from the official bar and un-officia1 bar is also utilized to complete the study.
Keywords: culpability; diminished responsibility; general exceptions; insanity defence; mental abnormality; psychological disorder